Embedding Tauhid in Everyday Life: A Study of Its Education and Effects on Female Students in Islamic Boarding Schools - Ahmad Abdillah Matinetta; Salwa Safira Choirunnisa; Muallimah Muallimah (South Sulawesi Education Development (SSED), 2023)
This study aims to explore tauhid education in students at Pondok Modern Darussalam Gontor Putri Campus 4. The focus of this research includes the description of tauhid education, the form of its implementation, as well as supporting and inhibiting factors. The study was conducted for one month using qualitative methods and a descriptive approach. The results showed that tauhid education can be learned and implemented through material taught by teachers, supported by homeroom teachers and dormitory managers. Implementation includes habituation of congregational prayer five times, Tahsinul Qiraah, and honesty in daily behaviour. Supporting factors include early parental guidance and teacher emphasis on applying tauhid daily. The inhibiting factors involve a lack of parental knowledge, busy schedules, and a lack of students' self-awareness. These findings provide insight into the complexity of tauhid education and the importance of an integrated approach involving various parties, including parents, teachers, and students, in daily life.